2021
DOI: 10.1021/acs.jpclett.1c01381
|View full text |Cite
|
Sign up to set email alerts
|

Acridones: Strongly Emissive HIGHrISC Fluorophores

Abstract: An acridone derivative (N-methyl-difluoro-acridone, NMA-dF) is characterized with respect to its utility as an emitter in organic light emitting diodes (OLEDs). Using steadystate and time-resolved spectroscopy as well as quantum chemistry, its ability to convert singlet and triplet excitons into light was scrutinized. NMA-dF emits in the deep blue range of the visible spectrum. Its fluorescence emission occurs with quantum yields close to 1 and a radiative rate constant of ≈5 × 10 8 s −1 . So, it processes sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“…TADF molecules that undergo rISC from a higher triplet state T n ( n > 1) to the emissive S 1 state (HIGHrISC) were thought to be one of the ideal materials to overcome the abovementioned problems. Under these circumstances, short exciton lifetime is guaranteed (key for long operation lifetimes) because rISC is much faster than the radiative decay and normal fluorescence lifetime is expected. Additionally, one could choose a molecule with large k rad in order to enhance the brightness of OLEDs . While novel materials are being developed, one kind of ketone with a xanthone structure (xanthone, thioxanthone, and acridone) was reported to show the interesting features above. There are four close-lying singlet and triplet ππ* and n O π* states ( 1 ππ*, 1 n O π*, 3 ππ*, and 3 n O π*, respectively) in these ketones.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…TADF molecules that undergo rISC from a higher triplet state T n ( n > 1) to the emissive S 1 state (HIGHrISC) were thought to be one of the ideal materials to overcome the abovementioned problems. Under these circumstances, short exciton lifetime is guaranteed (key for long operation lifetimes) because rISC is much faster than the radiative decay and normal fluorescence lifetime is expected. Additionally, one could choose a molecule with large k rad in order to enhance the brightness of OLEDs . While novel materials are being developed, one kind of ketone with a xanthone structure (xanthone, thioxanthone, and acridone) was reported to show the interesting features above. There are four close-lying singlet and triplet ππ* and n O π* states ( 1 ππ*, 1 n O π*, 3 ππ*, and 3 n O π*, respectively) in these ketones.…”
Section: Introductionmentioning
confidence: 99%
“…Acridone and its derivatives have very similar structures as xanthone and thioxanthone, and they have been widely applied in pharmaceutical development, new materials, and biological probes. Their fluorescence quantum yields were reported to be higher than those of xanthone and thioxanthone. , Recently, one acridone derivative ( N -methyl-difluoro-acridone), which emits blue fluorescence with a quantum yield of 0.87 in methanol, has been shown to have the ability to covert both singlet and triplet exactions into light even though no singlet–triplet equilibrium state is observed and thus it is potentially suitable as a blue OLED emitter . A previous theoretical study by Marian and Rai-Constapel suggested that equilibrium between 1 ππ* and 3 n O π* states could exist in acridone since ISC and rISC can take place on a picosecond timescale when it is in acetonitrile .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 This structural sensitivity has motivated recent research into synthetic modifications of acridone. [10][11][12][13]15 We speculated that incorporating a Lewis acid-base pair into acridone could be used as an alternative strategy to elicit ICT fluorescence (Scheme 1). 1-Hydroxy-10-phenylacridone (DY) can bind a Lewis acid, such as borondifluoride (BF 2 ) and metal ions, thereby creating a negative charge in the vicinity of the carbonyl unit.…”
mentioning
confidence: 99%
“…13 This structural sensitivity has motivated recent research into synthetic modifications of acridone. 10–13,15…”
mentioning
confidence: 99%